2017
DOI: 10.1186/s12871-017-0444-x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on significant hemodynamic changes caused by a high concentration of epidurally administered ropivacaine: correlation and prediction study of stroke volume variation and central venous pressure in thoracic epidural anesthesia

Abstract: BackgroundThoracic epidural anesthesia (TEA) exacerbates hypotension due to peripheral vasodilator effects following the use of general anesthetics. This study aimed to compare the hemodynamic changes caused by three different concentrations of epidural ropivacaine and to evaluate the performance of the stroke-volume variation (SVV) and central venous pressure (CVP) during TEA with general anesthesia.MethodsA total of 120 patients were administered 8 mL of ropivacaine solution via epidural injection, following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Moreover, previous studies and our study showed the association between EA and perioperative hemodynamic instability, leading to early termination in 7–41% of EA (10.5% in our study). 58,26,27 The higher cumulative fluid balances on PODs 1–3 in the EA group can be explained by the switch from vasoactive medication at the MC/IC to fluid therapy on the surgical ward to ensure adequate hemodynamic status. We hypothesize that excessive fluid therapy on the surgical ward is needed as long as the EA phase is prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies and our study showed the association between EA and perioperative hemodynamic instability, leading to early termination in 7–41% of EA (10.5% in our study). 58,26,27 The higher cumulative fluid balances on PODs 1–3 in the EA group can be explained by the switch from vasoactive medication at the MC/IC to fluid therapy on the surgical ward to ensure adequate hemodynamic status. We hypothesize that excessive fluid therapy on the surgical ward is needed as long as the EA phase is prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…The anesthesia manipulation was conducted according to the attending anesthesiologist's discretion. Since high concentration of epidurally administrated ropivacaine may cause a significant hemodynamic change [12,13], anesthesiologists in our medical center prefer to delivered lower concentration of ropivacaine in elder patients for more stable hemodynamic and to reduce potential perioperative cardiovascular complications Meanwhile, higher epidural ropivacaine concentration provided not only regional analgesia but also a better relaxation of abdominal muscles [14][15][16]. Thus, anesthesiologists in our medical center prefer to administrate high dose of ropivacaine in patients who received radical, complicated and time-consuming surgeries, such as pancreaticoduodenectomy in the present study.…”
Section: Exposure Variablementioning
confidence: 99%
“…High-dose or high-concentration epidural injection of local anesthetics might cause hypotension, bradycardia, nausea, anxiety, and other adverse reactions, which may induce cardiovascular events and central nervous system toxicity in elderly patients or patients with cardiovascular diseases (2). In addition, the block level of local anesthetics in elderly patients is much higher than that in younger patients and is often accompanied by motor block (3). To reduce the risks from epidural anesthesia in elderly patients, it is necessary to reduce the concentration of the local anesthetics, but too low a concentration may lead to an insufficient postoperative analgesic effect.…”
Section: Introductionmentioning
confidence: 99%